SIMULASI ALIRAN FLUIDA DENGAN VARIASI DIAMETER PIPA PESAT PADA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO SINDANG CAI - Dicky Rivaldi (2022)
Micro hydro power plant is a power plant that utilizes energy from the flow of water with small to medium discharge. This MHP has main components, penstock pipe, turbine, and generator. To be able to take full advantage of the flow of water, the selection of the diameter of the penstock pipe is one of the important things that affect the electrical energy produced. Because the speed and pressure given from each variation of the diameter of the penstock pipe rapidly produces different torques so that the electrical power produced is different. The research will be conducted using CFD simulation with variations in diameter of the penstock pipe 80 cm, 90 cm, 100 cm, 110 cm, and 120 cm which aims to determine the optimum power and efficiency of the MHP. The results of this simulation show that the use of a diameter of 80 cm produces a speed of 4,378 m/s, and a pressure of 240.000 Pa and a diameter of 120 cm produces a speed of 1,946 m/s and a pressure of 350.000 Pa. To get maximum power and efficiency, use a penstock pipe with a diameter of 90 cm which has a maximum pressure and speed, resulting in a torque of 12,625.88 Nm and a power generated of 792.905,30 watts with efficiency 91.94%.